Strategi Pemanfaatan Modal Non Ekonomi Dalam Pemenangan Kandidat Pada Pilkada Tahun 2020 Di Kabupaten Pohuwato - Bala; Sukri; Ariana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
This research was motivated by the political phenomenon of the 2020 Regional Elections in Pohuwato Regency, which was conquered by figures with inadequate economic and financial capital.  The purpose of this study is to understand and describe the strategy of maximizing the use of non-economic capital as part of the political strategy carried out to win in the regional election arena. The data collection method was conducted through documentation studies and in-depth interviews. Data analysis techniques consist of three steps: data reduction, data presentation, and conclusion drawing / verification. The results showed that the strategy of maximizing the capital was carried out by the winning figure with the strategy of understanding the habitude found among the Pohuwato people. So, from the results of the reading, it was concluded that the Pohuwato society is a plural society that upholds the prevailing customary values. The efforts are to build emotional closeness with traditional stakeholders and always keep every action from violating applicable customary values. The second strategy is the utilization of social capital by building trust, friendship, and loyalty, as well as owned social networks. The principle of leadership for all suggests that the figure of BC will stand above the interests of all factions. This strategy was developed in response to the condition of the plural Pohuwato society. The third strategy, the use of symbolic capital, was carried out by SM with his position as a representative of the local parliament, the support of his siblings as a Regents, the big family name Mbuinga, which is quite large and famous. Besides, the spouse of the deputy regent candidate is a female figure, former chairman of the Pohuwato Regency Parliament, a member of the Gorontalo Provincial Parliament, and she has a big family name in Pohuwato Regency.